Pengaruh Kualitas Pelayanan Perangkat Desa Berdasarkan Model SERVQUAL terhadap Kepuasan Masyarakat - Abdullah Rumeon; Zainal Abidin Rengifurwarin; Mike J. Rolobessy (MAN 4 Kota Pekanbaru, 2025)
This study examines the influence of village apparatus service quality, measured using the SERVQUAL model, on community satisfaction in Olong Administrative Village, North Seram District, Central Maluku Regency. The SERVQUAL model, covering tangibles, reliability, responsiveness, assurance, and empathy, serves to evaluate how well public services meet community expectations. Service quality in villages significantly affects trust, governance, and local development. This research identifies which dimensions most strongly affect community satisfaction and assesses whether village services meet public sector standards. Findings aim to provide practical insights for village governments, policymakers, and stakeholders to improve service quality, address gaps, and enhance residents’ experiences, thereby promoting more effective and responsive governance at the village level.